Pinkalicious : dragon to the rescue - Kann, Victoria (New York, NY : Harper, an imprint of Harper Collins Publishers, 2019)
When Pinkalicious and her friends try to roast marshmallows at a backyard camping party, it is too windy to keep the campfire lit, but luckily, Gertie the dragon steps in to help out.
Ages 4-8.
Keywords: Dragons -- Juvenile fiction; Campfires -- Juvenile fiction